The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.nepr.2020.102859
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-registration education on the motivation and preparation of midwifery students to work in continuity of midwifery care: An integrative review

Abstract: Access to continuity of midwifery care (CoMC) models in Australia is increasing but the capacity of the emerging midwifery workforce to provide this care remains largely unknown. The aim of this integrative literature review is to discover how well pre-registration midwifery education prepares and motivates Australian midwifery students to work in CoMC models when they enter practice. Following title review of 432 papers, removal of duplicates and review against the inclusion and exclusion criteria, nine paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Most students were provided with a positive learning environment which resulted in a rewarding and enriching learning experience. As confirmed by previous studies, continuity of midwifery placement within a continuity model allows for a holistic woman-centered approach to learning and provides unique and valuable facets of learning [37,51,56]. In addition, by placing students within a midwifery continuity model, they are exposed to the full scope of the role of the midwife and how midwives in that model support each other.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Most students were provided with a positive learning environment which resulted in a rewarding and enriching learning experience. As confirmed by previous studies, continuity of midwifery placement within a continuity model allows for a holistic woman-centered approach to learning and provides unique and valuable facets of learning [37,51,56]. In addition, by placing students within a midwifery continuity model, they are exposed to the full scope of the role of the midwife and how midwives in that model support each other.…”
Section: Discussionmentioning
confidence: 61%
“…This deepening awareness is supported by Gray et al [47] who suggests that students in caseload placements develop deep insight into how continuity works and how decisions and actions are centred around the woman. A recent integrative review by Cramer and Hunter [37], confirmed a connecting association between midwives working to full scope of practice building relationships with women and their sense of confidence and empowerment. Students who participated in the extended 6-month placement aligned with this world view when they talked about 'feeling like a midwife'.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Clinical support through mentorship in nursing gained momentum in the early 2000s when Andrew and Wallis (2001) fully unpacked the definitions, roles, preparation, and effectiveness of mentorship in nursing. Mentorship in midwifery allows midwifery students to practice the clinical skills necessary for the job and become well-orientated to the real-life experiences through the guidance of more experienced midwifery practitioners they work with during placement (Beukes and Nolte, 2013;Jamshidi et al, 2016;Bharj and Embo, 2018;Carter, Dietsch and Sidebotham, 2020). The purpose is to prepare students to achieve the required competencies during clinical placement and thus become safe and competent practitioners upon registration of the qualification (Hallas, Biesecker, and Newland, 2012;Lawson and Bunyan, 2013;Maxwell, Black, and Baillie, 2015).…”
Section: Clinical Support In the Post-millennium Phasementioning
confidence: 99%